2021
DOI: 10.1038/s41467-021-26566-4
|View full text |Cite
|
Sign up to set email alerts
|

Slow oxidation of magnetite nanoparticles elucidates the limits of the Verwey transition

Abstract: Magnetite (Fe3O4) is of fundamental importance for the Verwey transition near TV = 125 K, below which a complex lattice distortion and electron orders occur. The Verwey transition is suppressed by chemical doping effects giving rise to well-documented first and second-order regimes, but the origin of the order change is unclear. Here, we show that slow oxidation of monodisperse Fe3O4 nanoparticles leads to an intriguing variation of the Verwey transition: an initial drop of TV to a minimum at 70 K after 75 day… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 19 publications
(20 reference statements)
0
22
0
Order By: Relevance
“…Insight into the origin of the first and second order regimes of doped magnetites has recently been provided by a study of slow oxidation of magnetite nanoparticles . This revealed that the Verwey transition is initially suppressed to a minimum value at T V ≈ 80 K, but on further oxidation recovers to a persistent value of T V = 95 K as shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Insight into the origin of the first and second order regimes of doped magnetites has recently been provided by a study of slow oxidation of magnetite nanoparticles . This revealed that the Verwey transition is initially suppressed to a minimum value at T V ≈ 80 K, but on further oxidation recovers to a persistent value of T V = 95 K as shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“… Variation of the Verwey transition of magnetite nanoparticles with oxidation time in air from ref ( 52 ). Square, circle, triangle, and diamond symbols show T V values from magnetization ( M ), powder X-ray diffraction (XRD), NMR, and heat capacity ( C / T ) measurements, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations